A Study on Federation Clouds and its Issues - Keerthi, V; Anuradha, T (International Journal of Computer Sciences and Engineering, 2020)
Cloud computing which comprises various technologies from Infrastructure to Software services makes users to view computing in a new direction, as it is offering users a better IT services at low-cost. In case of collective usage of resources cloud providers that work collaboratively to form a federation of clouds or Inter-cloud. The federated cloud will address the issues like data availability, data loss, sharing of resources, data security etc. In case of resource sharing some of the applications require the credentials of the users or data to be shared between the federated clouds, which may lead to misuse of the identity, identification theft, and platform reliability. These issues are to be addressed in the federated cloud environment. An issue of security in cloud computing is an open research issue which also applied for federated clouds. In this paper we discuss some of the issues related to federation clouds and its impact on services are studied, new mechanisms and technique to be designed to reduce the risk is discussed.